Optimasi Konten Reels Instagram Sebagai Media Promosi untuk Meningkatkan Brand Awareness Menggunakan Aplikasi Capcut Pro pada Gun2 Bike - Batrisya Khazindar; Tri Ramadani Arjo; Joni Dwi Pribadi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Ofero Tulungagung is a brand focused on the sales of electric vehicles (e-vehicles) and is located in Tulungagung Regency. Up to this point, Ofero has relied heavily on social media, especially Instagram, as the primary platform for promotion. However, there has been lack of a structured and planned digital promotional strategy, especially in the form of video content. This research aims to design and produce promotional video content through Instagram Reels using the CapCut Pro application, as well as to measure the effectiveness of social media use in building a professional brand image for Ofero Tulungagung. This study employs the Action Research method, which consists of planning, action, observation, and reflection. The promotional material focuses on Instagram Reels videos that are informative and tailored to the target market, produced using CapCut Pro. Effectiveness was evaluated using the EPIC Model and Customer Response Index (CRI), resulting in an EPIC score of 4.50 and a CRI response of 62.6%. Instagram Insights showed reach increased to 1,500 accounts (953%), impressions reached 2,900 (872%), and interactions totaled 105, with engagement rates between 3.5% and 6%. The results indicate that Instagram Reels is an effective promotional medium for enhancing brand awareness. Future researchers should develop more interactive content, expand promotional platforms, and maintain consistent uploads. Direct audience engagement, such as replying to comments, polls, and Q&A sessions, is also essential to build connection and brand loyalty.